Hospitality and tourism development in cross River State, Nigeria: a case study of Obudu mountain resort (2019)
Over the past decades, tourism has experienced continued expansion and diversification, becoming one of the largest and fastest-growing economic sectors in the world. Many new destinations have emerged, challenging the traditional ones in Europe and North America. The continuous growth of the international tourism market makes it significantly more competitive than ever and raises the need to prioritise the development of hospitality facilities to ensure tourists’ comfortability at various tourism destinations. This article examines the hospitality’ facilities at Obudu Mountain Resort, Cross River State, Nigeria with a view to establishing the extent to which they contribute to tourists' comfortability and subsequently tourism development in Cross River State, Nigeria. Qualitative and quantitative methodologies were used. Findings were analysed using descriptive statistical tools of frequency> counts, simple percentages and tables for quantitative data while qualitative data were analysed descriptively. The article established that hospitality facilities such as the canopy walk way, the cable car, the landscape, well-equipped mountain villas, coupled with the serene environment and unique climatic condition at the resort provide complete touristic experience for the tourists. Majority of the respondents are of the opinion that these facilities contribute the most to their decision to choose the resort for holiday. To ensure the sustainability of these facilities, the state government outsourced the maintenance of some of these facilities. This management strategy ensures sustainability of the resort and their continuous patronage by tourists. The article concludes that hospitality facilities when managed properly contribute to tourism development as exemplified in Obudu Mountain Resort. The resort also significantly contributes to tourism development in Cross River State and in Nigeria.